Development of Sundanese Gamelan Ethnomathematics E-Module for Junior High School Mathematics Learning - Supriyadi, Edi; Turmudi, T.; Dahlan, Jarnawi Afgani; Juandi, Dadang (UUM PRESS, 2024)
Purpose – This study aimed to conduct a needs analysis for developing the ethnomathematics e-module based on Sundanese Gamelan to facilitate mathematics learning in junior high school. Specifically, this study identified crucial components for module development and to gather feedback from both students and teachers regarding the learning material. Methodology – The Research and Development (R&D) method was used, specifically the Plomp model, to create e-module for mathematics learning. Qualitative data were collected from ethnomathematics experts, a mathematics teacher, and five students via purposive sampling. The instruments used for this data collection included expert validation sheets, student interview recordings, teacher questionnaires, and small group observations Findings – The results indicated that the integration of Sundanese Gamelan ethnomathematics into junior high school mathematics e-module significantly improved students’ understanding and interest in the subject. This culturally infused approach increased students’ motivation and engagement, indicating a potential shift towards more inclusive and culturally responsive educational practices. Significance – The integration of Sundanese Gamelan ethnomathematics into mathematics curriculum is known for the unique blend of cultural elements with academic content, contributing to enhanced students’ understanding and cultural awareness. In addition, this method offered benefits for students, teachers, curriculum developers, and ethnomathematics researchers, presenting a holistic model that combined educational innovation with cultural appreciation